Pengaruh Ukuran Perusahaan, Profitabilitas, Financial Leverage dan Kepemilikan Institusional Terhadap Perataan Laba Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2009-2013 - Zulia Oviani; Errin Yani Wijaya; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The tedency of user’s financial report are contained the profit of profit and loss report. In the meantime manager, appraised his performance based on the information of profit and loss report. Until the appearance of profit management. Income smoothing is profit fluctuation decrease year by year to transferring income from high revenues to the unfavorable period. As a consequence, financial report were presented to the users of financial report couldn’t relied. Examples of cases that occur as a result of income smoothing among others, the case overseas, namely System Software Associates, Inc. AAER No. 1285, occurred on 14 July, 2000. They recognize revenue on income that is not clear whether the product has been shipped or the customer received yet. Revenue section of the income statement. Recognize revenue unclear as revenue in the fall. So that recognizes the revenue earnings presented in the financial statements is relatively stable as in previous years so as to attract investors to invest their funds.The research’s result are the profitability and institutional ownership affects to the income smoothing. While the firm size and financial leverage doesn’t affect to the income smoothing. Simultaneously firm size, profitability, financial leverage and institutional ownership affect to the income smoothing.Keywords : Firm Size, Profitability, Financial Leverage, Institutional Ownership, Income Smooting